2022
DOI: 10.55980/esber.v1i1.17
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of arrangement of treasury archives in preventing fraud at regional financial and revenue management agency

Abstract: This research aims to test the influence of the implementation of disbursement information systems, the arrangement of treasury archives, and leadership support for fraud prevention in the financial and revenue management agency of West Sulawesi province.  This research approach uses a descriptive quantitative approach. The population of this study is the head of subsection and head of the financial subfield and treasurer of each the financial and revenue management agency of West Sulawesi province. The sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…At this point, international antecedents were presented; in Indonesia: Rasmadi et al (2021) revealed that the variables of fund disbursement, file structuring, and management support had a significant impact on preventing fraud in the West Sulawesi Regional Revenue and Financial Management Agency, both partially and simultaneously.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At this point, international antecedents were presented; in Indonesia: Rasmadi et al (2021) revealed that the variables of fund disbursement, file structuring, and management support had a significant impact on preventing fraud in the West Sulawesi Regional Revenue and Financial Management Agency, both partially and simultaneously.…”
Section: Literature Reviewmentioning
confidence: 99%